2015
DOI: 10.1016/j.conbuildmat.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of GFRP-concrete hybrid beams with low degree of shear connection

Abstract: 11Recent developments in the design of advanced composite materials for construction have led researchers to 12 create novel high-performance structural elements that combine fiber-reinforced polymer (FRP) shapes with 13 traditional materials. The current study analyzes the experimental structural response of eight hybrid beams 14 made of pultruded glass FRP (GFRP) profiles mechanically connected to reinforced concrete (RC) slabs, 15 suitable for building floors as well as footbridge and marine pier superstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Pagliolico et al made a preliminary study on light transmittance properties of translucent concrete panels with coarse waste glass inclusions[130]. Neagoe et al made an experimental study of GFRP-concrete hybrid bems with low degree of shear connection[131]. Das et al gave a report on the flexural fracture response of a novel iron carbonate matrix-glass fibre composite and its comparison to Portland cement-based composites[132].…”
mentioning
confidence: 99%
“…Pagliolico et al made a preliminary study on light transmittance properties of translucent concrete panels with coarse waste glass inclusions[130]. Neagoe et al made an experimental study of GFRP-concrete hybrid bems with low degree of shear connection[131]. Das et al gave a report on the flexural fracture response of a novel iron carbonate matrix-glass fibre composite and its comparison to Portland cement-based composites[132].…”
mentioning
confidence: 99%
“…Regarding more specific tests on the connection between FRP profiles and concrete parts, Gonilha et al (2014) [13] performed several push-out tests and simulations of hybrid systems for a girder with I-shaped GFRP beams and concrete. Six specimens connected with steel bolts and/or bonding were considered in Koaik et al [14], and I-shaped pultruded GFRP bolt-connected profiles with partial interaction can be found in Neagoe et al [15]. The specific performance of FRP-concrete sections was also experimentally analyzed by Zou et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the bond coefficient and elastic modulus (E) of FRP were the main factors manipulating the GFRP-RC beam behaviour. Due to the low values of E and shear modulus (G) of FRP, the arrangement of GFRP profiles with concrete features to resist high loads using a stiffer hybrid structure was a good recommended solution [31][32][33][34][35][36][37][38][39][40][41]. From the above review, it can be concluded that most previous studies focused on the analysis of RC beams with GFRP bars.…”
Section: Introductionmentioning
confidence: 99%